Expertise-dependent perceptual performance in chess tasks with varying complexity - Küchelmann, Thomas; Velentzas, Konstantinos; Essig, Kai; Koester, Dirk; Schack, Thomas (Frontiers in Psychology, 2022)
Perceptual performance, anticipating opponents’ strategies and judging chess positions especially in subliminal processing is related to expertise level and dependent from chunking processes. It becomes obvious that chess expertise is a multidimensional phenomenon related predominantly to experience. Under consideration of chess expertise taxonomy we conducted two prime-experiments expanding existing designs by gradual increase of the target and task complexity. The main aim was the evaluation of potential visuocognitive limitations. The results reveal experts’ perceptual superiority manifested by fastest reaction times in case of increased stimulus and task complexity. Further, experts’ priming effects seem to be affected by the target content and/or priming duration. For short prime duration, experts show priming effects for less complex target content only. Interestingly, for longer prime duration and more complex target content, all participants reveal priming effects. In summary, we argue that experts’ visuocognitive processing (i.e. detecting or anticipating potential threats to the king) is rooted in better visual cognition due to stored chunks of checking and mating constellations. We suggest that visuocognitive limitations are related also to the target complexity as well to the task. Further investigate must be conducted in order to elucidate the factors with an increased impact on chess players’ performance.